2020
DOI: 10.1042/bsr20190209
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the vascular endothelial growth factor polymorphisms associated with the risk of pre-eclampsia

Abstract: Backgroud: Pre-eclampsia (PE) is a common pregnancy-induced hypertension disease. Some case–control studies reported the association between vascular endothelial growth factor (VEGF) gene polymorphisms (rs3025039, rs2010963) and PE risk. However, these associations were inconsistent in several studies. Therefore, we conducted this meta-analysis to assess the role of VEGF gene polymorphisms in PE more precisely. Methods: Eligible studies were searched in PubMed, Embase, Web of Science and Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…59 Over time, it has also been used to describe scenarios where other health outcomes are better than expected among Hispanic women. 57,60 The Role of Race and Ethnicity on the Pathophysiology of Preeclampsia Abnormalities of placental formation and development, 61e63 immunologic factors, 64,65 vascular changes, 66 and inflammation have all been identified as contributing to the pathophysiology of preeclampsia. 67 There has been a desire to investigate genetic causes of preeclampsia.…”
Section: Expert Reviewmentioning
confidence: 99%
“…59 Over time, it has also been used to describe scenarios where other health outcomes are better than expected among Hispanic women. 57,60 The Role of Race and Ethnicity on the Pathophysiology of Preeclampsia Abnormalities of placental formation and development, 61e63 immunologic factors, 64,65 vascular changes, 66 and inflammation have all been identified as contributing to the pathophysiology of preeclampsia. 67 There has been a desire to investigate genetic causes of preeclampsia.…”
Section: Expert Reviewmentioning
confidence: 99%
“…In 2017, Yu and colleagues found no statistically significant difference in the genotype and allelic frequencies of VEGF rs699947 and rs1570360 between COPD patients and control groups [39]. We investigated the relationship between VEGF rs3025039 and COPD as we found a wide range of studies that focused on this polymorphism and its relationship with various diseases, like pre-eclampsia [40], extracranial internal carotid artery stenosis and ischemic stroke [41], and bladder cancer [42], but only one study that described its involvement in COPD. Baz-Davila et al investigated the potential role of several SNPs in the susceptibility and progression of COPD in a Spanish population and found no association between rs3020539 and COPD [43].…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis by Duan et al found that VEGF gene rs3025039 T and rs2010963 C alleles significantly increased the risk of PE in the study population 31 . Additionally, subgroup analyses demonstrated that the two polymorphic alleles were associated with PE risk in Chinese and Caucasian populations, respectively 31 . Wang et al 32 also found that rs3025039 T and rs2010963 C alleles were closely associated with PE in Asian and European populations, respectively, but neither rs699947C/A nor rs1570360G/A was associated with PE risk in the included populations.…”
Section: Genetic Polymorphisms Of Pihmentioning
confidence: 99%